PRODUKTIVITAS DOSEN (Kajian Faktor-Faktor Penduga Diketahui) - Sutrisno, Budi; Mulyani, Sri (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this research is to know: (1) organizational climate influence to lecturer productivity; (2) satisfaction influence work to lecturer productivity; (3) interest influence to lecturer productivity; (4) motivation influence to lecturer productivity; and (5) influence by simultaneous between organizational climate, work satisfaction, interest, and motivate to lecturer productivity. Research Method used is quantitative method by causal design. This research population is all lecturers remain at Veteran Bangun Nusantara University of Sukoharjo a number of1 09 people. Research sample counted 86 one who is taken by using formula from Slovin, and to each faculty taken by proportional. Data collecting technique uses the questioner. The data are analyzed by Double Regress. The result indicates that: (1) organizational climate gives positive and significant influence to lecturer productivity. Level of influence gives a organizational climate to visible lecturer productivity through the equation of regress Y = 5,105 + 0,505X1; (2) work satisfaction gives positive and significant influence to lecturer productivity. Level of influence is a work satisfaction to visible lecturer productivity through the equation of regress Y = 5,105 + 0,425X2; (3) interest gives positive and significant influence to lecturer productivity. Level of influence is given by interest to visible lecturer productivity through the equation of regress Y = 5,105 + 0,594X3; (4) motivation positive and significant influence to lecturer productivity. Level of influence is given by motivation to visible lecturer productivity through the equation of regress = 5,105 + 0,479X4; (5) there is simultaneous in organizational climate, work satisfaction, interest, and motivate to have an effect on lecturer productivity. This matter is proved from result F test, got F calculated 124,802 with the level significance 0,000. Level of influence by simultaneous are organizational climate, work satisfaction, interest, and motivate to have an effect on to lecturer productivity is equal to 86%, the rest that is 14% representing incoming influence from other factor.